2014
DOI: 10.1097/ico.0000000000000149
|View full text |Cite
|
Sign up to set email alerts
|

Pterygium Is Related to a Decrease in Corneal Endothelial Cell Density

Abstract: Pterygium is related to a decrease in corneal ECD. Surgical intervention should be considered in patients with extensive pterygium involvement in the cornea or a significant increase in astigmatism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 18 publications
4
29
2
Order By: Relevance
“…However, the results of our study came to a different conclusion. The ECD decrease in eyes with pterygium from our retrospective study was far less (76 cells/mm 2 , 3.1%) than those in the previous studies [11, 13, 15]. In our retrospective study, the ECD of eyes with unilateral pterygium was almost the same as the ECD of the contralateral eyes.…”
Section: Discussioncontrasting
confidence: 57%
See 4 more Smart Citations
“…However, the results of our study came to a different conclusion. The ECD decrease in eyes with pterygium from our retrospective study was far less (76 cells/mm 2 , 3.1%) than those in the previous studies [11, 13, 15]. In our retrospective study, the ECD of eyes with unilateral pterygium was almost the same as the ECD of the contralateral eyes.…”
Section: Discussioncontrasting
confidence: 57%
“…Theoretically, these mediators and ultraviolet light may also damage corneal endothelium cells (ECC) and corneal endothelial cell density (ECD) may be decreased in eyes with pterygium [10]. Although results from previous clinical studies were consistent with this theory [1113], in our cataract clinic we found that the preoperative ECD was not significantly decreased in cataract eyes with primary pterygium compared to those without pterygium. We speculated that pterygium might not be associated with ECD decrease in our population.…”
Section: Introductionmentioning
confidence: 54%
See 3 more Smart Citations